Ketogenic dietary therapies in epilepsy: recommendations of the Italian League against Epilepsy Dietary Therapy Study Group - De Giorgis, Valentina; Tagliabue, Anna; Bisulli, Francesca; Brambilla, Ilaria; Camerini, Alessandra; Cusmai, Raffaella; Darra, Francesca; Dianin, Alice; Domenica, Elia; Lodi, Monica Anna Maria; Matricardi, Sara; Messana, Tullio; et al. (Frontiers in Neurology, 2023)
A stepwise increase in the utilization of ketogenic dietary therapies for drug-resistant epilepsy has been observed in Italy in the last decade, although it is still considered often underused in many centers when compared to other countries. The Dietary Therapy Study Group of the Italian League against Epilepsy proposes practical recommendations to improve shared knowledge and facilitate the application of ketogenic dietary therapies, optimizing its efficacy and tolerability. The experts involved (11 child neuropsychiatrists, two adult neurologists, one psychologist, one pharmacologist, one pediatric endocrinologist, one representative of patients' associations, and three dietitians and clinical nutritionists) responded to a survey on current clinical practice issues and were asked to discuss controversial topics related to supplementation, long-term maintenance, transition, and a multidisciplinary approach to ketogenic dietary therapies. Practical indications for patient selection, diet initiation, management, side effects prevention, and follow-up are provided.